Synthesis, adsorption and analytical applicability of Ni-imprinted polymer for selective adsorption of Ni2+ ions from the aqueous environment. (August 2019) - Kumar, Ameet; Balouch, Aamna; Abdullah,; Pathan, Ashfaque Ahmed
Abstract: A novel nickel imprinted polymer (Ni-IP) was synthesized by using precipitation polymerization method with 4-vinyl pyridine as ligand and methacrylic acid as functional monomer and it was employed to eliminate the nickel (II) ions from the aqueous media. In this work, various effects of preparation conditions on adsorption performance were also investigated. Several ligands, functional monomers, and cross-linkers were employed in the polymerization process to obtained maximum adsorption capacity. The synthesized Ni-IP was characterized by scanning electron microscopy (SEM), energy dispersive x-ray analysis (EDX) and Fourier transform infrared spectroscopy (FT-IR). Several parameters i.e. pH, adsorbent dose, agitation time and shaking speed were optimized to obtained maximum adsorption capacity. The maximum adsorption capacity of Ni-IP was 125 mg/g and obtained in 6min of agitation time with the concentration of 5 mg/L at pH 6.0. The kinetic data were well described by pseudo-second-order while Langmuir model is best fitted to isotherm data. The relative standard deviation, the limit of detection and quantification of this method was found to be 4.2%, 0.85μg/L and 2.83μg/L. The relative selective coefficient of Ni 2+ ions and selective ions are greater than one due to the imprinting effect. This Ni-IP polymer also possesses good reproducibility and stability.